On Estimates for the Period of Solutions of Equations Involving the ϕ-Laplace Operator - Acinas, Sonia Ester (2014)
In this paper we give new bounds for the period of solutions to certain Hamiltonian system involving a function ϕϕ. We also obtain upper and lower bounds which are uniform with respect to the function ϕϕ. Furthermore, the optimality of this lower bound is established.